Mid-year review of the Indian economy 2003 - 2004 - Bery Suman K (New Delhi Shipra, 2004)
The India international centre's annual mid-year review of the Indian economy is strategically timed to permit analysis of trends in the current fiscal year before budget preparations for the next year get underway. This year's review comes at a time whe
Keywords: Economic conditions; India